Animal Tropology as a Means to Present Refugee Issues i n Children’s Literature (In the 21st Century - Bednarek, Magdalena (Porównania, 2025)
The paper examines the presence of animal figures in contemporary children’s books about migrants. The point of departure in this article is the long tradition of using animals in children’s fiction. Nevertheless, in this case it can be described as an Aesopian convention of presenting difficult and politically fraught problems in a concealed form. Telling stories about animals instead of describing human experience provides an opportunity to present difficult and horrifying situations in a form acceptable for young readers; however, it also poses a threat of unjustified simplification and false comparisons. The author classifies forms of animal figures in children’s books about migration into three types based on the rhetorical figures used. Anthropomorphism, metonymy and comparison are the rhetorical devices through which animals appear in children’s fiction about migrant experience. The author puts a lot of emphasis on showing that the presence of animals is used to promote pro-migrant attitudes as well as to soften the terror of migrant experience. The aim of this paper is to establish the connection between these aims and the types of representation of migrants in the form of animals.